Development of Atomoxetine-Loaded NLC In Situ Gel for Nose-to-Brain Delivery: Optimization, In Vitro, and Preclinical Evaluation - Dibyalochan Mohanty; Omar Awad Alsaidan; Ameeduzzafar Zafar; Trishala Dodle; Jeetendra Kumar Gupta; Mohd Yasir; Anshuman Mohanty; Mohammad Khalid (MDPI AG, 2023)
The present study investigates the brain-targeted efficiency of atomoxetine (AXT)-loaded nanostructured lipid carrier (NLC)-laden thermosensitive in situ gel after intranasal administration. AXT-NLC was prepared by the melt emulsification ultrasonication method and optimized using the Box-Behnken design (BBD). The optimized formulation (AXT-NLC) exhibited particle size PDI, zeta potential, and entrapment efficiency (EE) of 108 nm, 0.271, −42.3 mV, and 84.12%, respectively. The morphology of AXT-NLC was found to be spherical, as confirmed by SEM analysis. DSC results displayed that the AXT was encapsulated within the NLC matrix. Further, optimized NLC (AXT-NLC13) was incorporated into a thermosensitive in situ gel using poloxamer 407 and carbopol gelling agent and evaluated for different parameters. The optimized in situ gel (AXT-NLC13G4) formulation showed excellent viscosity (2532 ± 18 Cps) at 37 °C and formed the gel at 28-34 °C. AXT-NLC13-G4 showed a sustained release of AXT (92.89 ± 3.98% in 12 h) compared to pure AXT (95.47 ± 2.76% in 4 h). The permeation flux through goat nasal mucosa of AXT from pure AXT and AXT-NLC13-G4 was 504.37 µg/cm2·h and 232.41 µg/cm2·h, respectively. AXT-NLC13-G4 intranasally displayed significantly higher absolute bioavailability of AXT (1.59-fold higher) than intravenous administration. AXT-NLC13-G4 intranasally showed 51.91% higher BTP than pure AXT (28.64%) when administered via the same route (intranasally). AXT-NLC13-G4 showed significantly higher BTE (207.92%) than pure AXT (140.14%) when administered intranasally, confirming that a high amount of the AXT reached the brain. With the disrupted performance induced by L-methionine, the AXT-NLC13-G4 showed significantly (p < 0.05) better activity than pure AXT as well as donepezil (standard). The finding concluded that NLC in situ gel is a novel carrier of AXT for improvement of brain delivery by the intranasal route and requires further investigation for more justification.